Implementasi Core Values Dan Employer Branding ASN Dalam Upaya Meningkatkan Kinerja Aparatur Sipil Negara : Studi Kasus Pada Dinas Ketahanan Pangan, Pertanian Dan Perikanan Kota Banjar - Doni Indratno; Enas Enas; Oyon Saryono (International Forum of Researchers and Lecturers, 2024)
The core value of ASN BerAKHLAK and employer branding ASN were inaugurated by the President of the Republic of Indonesia on July 27, 2021. Core Value ASN BerAKHLAK stands for Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative. The purpose of launching ASN Core Value is to standardize basic values for all civil servants in Indonesia so that it can become the foundation of a quality, dignified and professional ASN work culture. While ASN's employer branding